DEVELOPMENT PROSPECTS ENLARGEMENT BUSINESS OF NILA FISH (OREOCHROMIS NILOTICUS) IN MARSAWA VILLAGE SENTAJO RAYADISTRICT KUANTAN SINGINGI REGENCY RIAU PROVINCE - Saputra, Elpas; Yulinda, Eni; Arief, Hazmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted in September 2017 located in Marsawa Village Sentajo Raya District at Kuantan Singingi in Riau Province. This study aims to determine the amount of investment and profit, analyze business feasibility, and review the prospects of business development of Nila fish enlargement. The method used in this research is case study. Respondents taken in this research are business owner of enlargement and labor. Based on the results of research Investment cultivation of fish farmers in the village of Marsawa IDR. 1.272.260.000-. consisting of fixed capital of IDR. 38,640,000. and working capital of Rp. 1.233.620.000 . Result of feasibility analysis in get profit equal to IDR. 451.453.333 per year from all cultivators in the village Marsawa and net income average cultivators 1 harvest is IDR. 3,009,688-. RCR 1,3 FRR 35%, PPC 2.8 years. The business development prospect of the enlargement in Marsawa Village is quite good, based on the criteria of investment, marketing, and fulfillment of all sub-systems of agribusiness (supplay input subsystem, farming subsystem, and marketing subsystem)Keyword: Prospects, Nila, Marsawa Village,